The White House and the Kyoto Protocol: Double Standards on Uncertainties and Their Consequences - Philippe Tulkens; Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper compares the level of uncertainty widely reported in climate change scientific publications with the level of uncertainty of the costs estimates of implementing the Kyoto Protocol in the United States. It argues that these two categories of uncertainties were used and ignored, respectively, in the policy making process in the US so as to challenge the scientific basis on the one hand and on the other hand to assert that reducing emissions would hurt the economy by an amount stated without any qualification. The paper reviews the range of costs estimates published since 1998 on implementing the Kyoto Protocol in the US. It comments on the significance of these cost estimates and identifies a decreasing trend in the successive estimates. This implies that initially some of the most influential economic model-based assessments seem to have overestimated the costs, an overestimation that may have played a significant role in the US decision to withdraw from the Protocol. The paper concludes with advocating that future economic estimates always include uncertainty ranges, so as to be in line with a basic transparency practice prevailing in climate science.
Keywords: Q5; Q54; Q58; C82; 330; United States; Kyoto Protocol; Cost Estimates; Uncertainties; Umweltabkommen; Klimaschutz; Umweltkosten; USA